Cytoreductive surgery plus chemotherapy versus chemotherapy alone for recurrent epithelial ovarian cancer - Galaal, Khadra (John Wiley & Sons, Ltd, 2010)
BACKGROUND: Most women with advanced epithelial ovarian cancer will ultimately develop recurrent disease after completion of initial treatment with primary surgery and adjuvant chemotherapy. Secondary cytoreductive surgery may have survival benefits in selected patients. However, a number of chemotherapeutic agents are active in recurrent ovarian cancer and the standard treatment of patients with recurrent ovarian cancer remains poorly defined. OBJECTIVES: To evaluate the effectiveness and safety of secondary surgical cytoreduction and chemotherapy compared to chemotherapy alone for women with recurrent epithelial ovarian cancer. SEARCH METHODS: We searched the Cochrane Gynaecological Cancer Group Trials Register, The Cochrane Register of Controlled Trials, (CENTRAL) Issue 1 2009, MEDLINE and EMBASE up to February 2009. We also searched registers of clinical trials, abstracts of scientific meetings, reference lists of review articles and contacted experts in the field. SELECTION CRITERIA: We searched for RCTs, quasi‐randomised trials and non‐randomised studies that compared secondary cytoreductive surgery and chemotherapy to chemotherapy alone in women with recurrent epithelial ovarian cancer. DATA COLLECTION AND ANALYSIS: Three reviewers independently assessed whether potentially relevant studies met the inclusion criteria. No trials were found and therefore no data were analysed. MAIN RESULTS: The search strategy identified 1431 unique references of which all were excluded on the basis of title and abstract. AUTHORS' CONCLUSIONS: We found no evidence from RCTs to inform decisions about secondary surgical cytoreduction and chemotherapy compared to chemotherapy alone for women with recurrent epithelial ovarian cancer. Ideally, a large randomised controlled trial or, at the very least, well designed non‐randomised studies that use multivariate analysis to adjust for baseline imbalances are needed to compare these treatment modalities. The results of the ongoing RCT AGO‐OVAR OP.4 (DESKTOP III) is awaited.